State and local finances under pressure - Sjoquist, David L. (Cheltenham, UK ; Northhampton, MA, USA : E. Elgar, 2003)
This book explores the future of state and local government fiscal systems given the numerous pressures they face from economic, legal, technlogical, demographic and political forces.
Includes bibliographical references and index.
osa 03/06/14; oif 27/01/15
Loans
Keywords: Local finance -- United States; Finance, Public -- United States -- States; Intergovernmental fiscal relations -- United States